Privatisasi penuh apakah lebih baik daripada privatisasi sebagian? - Rasyid, Rafki (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the differences in financial performance between a fully privatized company, namely PT Indosat, compared to a partially privatized company, namely PT Telkom. The study uses the difference in differences (DiD) method in relation to looking at the effect of the economic crisis that occurred due to the Covid-19 pandemic on companies that have not been privatized compared to companies that have been privatized. This study uses a comparative analysis method by comparing the financial performance of PT Indosat, Tbk with PT Telkom (Persero), Tbk from 2005 to 2020. The performance of the two companies will be compared by calculating the financial ratios of profitability ratios. between PT Telkom and PT Indosat and found no difference in performance when the economic crisis occurred compared to when the economic crisis occurred.